Bridging the gaps of headache care for underserved populations: Current status of the headache field in Latin America. (September 2022) - Lisicki, Marco; Souza, Marcio Nattan Portes; de Oliveira, Arão Belitardo; Rubio-Beltrán, Eloísa; Labastida-Ramirez, Alejandro; Ashina, Messoud; Peres, Mario
Objective: To evaluate the current status of specialized headache care and research in Latin America. Background: Latin America corresponds to about 9% of the global population. There is considerably limited access to headache services, and very few resources are allocated to headache research in this region. Methods: The study consisted of two parts. First, in order to evaluate headache-related scientific output from Latin American countries we performed a 10-year bibliometric analysis and contrasted the results with a human developmental index–adjusted projection model. Secondly, we conducted a survey addressing different aspects of headache research, education, clinical practice, and awareness among members of the Latin American Headache Society. Results: During the last 10 years 70% of Latin American countries published less than three articles regarding headache disorders. This contrasts with an average expected publication rate of 889 scientific papers. Indeed, none of the countries fulfilled their human developmental index – adjusted projected scientific output, with Brazil being the closest reaching 84.1% of what would be considered optimal according to the model. From the 86 headache-dedicated professionals that responded to the survey, most (64%) reported not having a headache specialization programme of any kind available in their countries. The biggest impediments towards conducting research observed by participants were the lack of time (39%), resources (22%), and training (21%). Conclusions: Latin American countries have a considerable gap in headache-related scientific production, and also in formal education, research, and implementation of multidisciplinary services. Access to specialized headache care is particularly limited for patients with lower economic income.